2020
DOI: 10.1037/ppm0000256
|View full text |Cite
|
Sign up to set email alerts
|

Associations between parental media monitoring, media use, and internalizing symptoms during adolescence.

Abstract: Although time spent using media has been linked to internalizing problems, few studies have explored the role that parents might play in these associations. The current study explored how controlling and autonomy-supportive restrictive and active parental media monitoring were associated with adolescents’ internalizing problems via time spent using media (media multitasking, social media, TV, video games, music, reading, texting, and Internet). The current study used data from a national study of teens aged 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…The results of a meta-analysis also showed that social media use can negatively affect offline family communication (Tadpatrikar et al, 2021 ). The social function of people with long-term Internet addiction will further deteriorate, leading to more internalized problems, such as suicide and depression (Padilla-Walker et al, 2020 ).…”
Section: Problematic Internet Use and Parent-child Relationshipmentioning
confidence: 99%
“…The results of a meta-analysis also showed that social media use can negatively affect offline family communication (Tadpatrikar et al, 2021 ). The social function of people with long-term Internet addiction will further deteriorate, leading to more internalized problems, such as suicide and depression (Padilla-Walker et al, 2020 ).…”
Section: Problematic Internet Use and Parent-child Relationshipmentioning
confidence: 99%
“…This creates dilemmas for parents to heavy gamers. While worry has been found to correlate with restrictive practices and negatively with supportive behaviors ( Lieberoth and Lundsgaard, 2020 ), autonomy supporting parenting approaches seem to enhance acceptance of rules and reduce media use among teens ( Padilla-Walker et al, 2019 ; Weinstein and Przybylski, 2019 ). Yet parents struggle to judge appropriate levels of “screen time,” and popular concern augmented through media is a driver of policy preference and even research priorities in mental health and substance abuse domains ( Hallam, 2002 ; Slater et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…The media practice model (MPM; Steele & Brown, 1995; see also Padilla-Walker et al, 2020), which posits that individual differences and developmental experiences (e.g., peer, familial, and demographic backgrounds) can shape young people's identities in relation to the media they chose to consume-and how the selected media in turn shape their attitudes and behaviors-served as an organizing framework for our study. Because our research examined the content of teen romantic movies and their outcomes, we focused on the interaction aspect of the MPM, which highlights the psychological and behavioral components of media engagement, including interpretation and evaluation of media content.…”
Section: Theoretical Perspectives and Research Questionsmentioning
confidence: 99%